Optimization of the Refractory Lining Life of Copper Converters - A. J. Rigby (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
The wear mechanisms of the tuyere lines of Peirce-Smith and Hoboken converters are a subject of endless debate and speculation. However, there has been an indication that one of the primary factors in the deterioration of tuyere lines is due to the batch operation of the converting process. The cooling of the brick in the tuyere line during out-of-stack times leads to shrinkage of the brick and resultant opening of the joints. Subsequently, on re-entry of the tuyere line into the bath, the joints become penetrated with matte and re- expansion of the brick is prevented. It is thought that this regular cycle of exiting the batch for slag skimming and replenishment of matte and re-entering for further blowing leads to a gradual “ratcheting” of the tuyere brick lining. If no expansion allowance is furnished between the endplate and the endwall of the lining, then the generation of damaging compressive stress is unavoidable. INTRODUCTION It is generally accepted industry-wide that the integrity of a refractory lined vessel is determined by an inextricable combination of refractory brick quality, the caliber of the lining design and installation, and the severity of the process inflicted upon the high wear areas of the vessel lining. Rigby has summarized the concentrated attempt, over the past several years, to optimize the microstructural, chemical, and fracture properties of the refractories used in non-ferrous pyrometallurgical vessels. Furthermore, lining design concepts involving larger and longer brick and the extent and positioning of expansion allowance in the joints have been extensively trialed. All these efforts have provided some, but not startling, improvements. The simple fact is that a vessel lining composed of bricks with an optimized microstructure and chemical inertness must installed with a well-conceived design to decompress the lining stresses that are generated by the batch operation of copper converters. REFRACTORY QUALITY Converting is conducted by injecting air into the molten matte and white metal for the very purpose of generating iron and copper oxide slags. These slags must be contained by a refractory which, by its mineralogical formulation, is optimized for chemical inertness.